Cord blood mononuclear cells prevent neuronal apoptosis in response to perinatal asphyxia in the newborn lamb. (14th December 2015) - Aridas, James D. S.; McDonald, Courtney A.; Paton, Madison C. B.; Yawno, Tamara; Sutherland, Amy E.; Nitsos, Ilias; Pham, Yen; Ditchfield, Michael; Fahey, Michael C.; Wong, Flora; Malhotra, Atul; Castillo‐Melendez, Margie; et al.
Abstract : Key points: Asphyxia at the time of birth is a significant cause of death or disability in newborns. There is very limited treatment available for these newborns. Autologous umbilical cord blood (UBC) mononuclear cells reduce clinical markers of brain damage following perinatal asphyxia. Autologous UBC mononuclear cells reduce neuroinflammation and neuronal apoptosis within the brain following perinatal asphyxia. Autologous UBC mononuclear cells administered 12 h after perinatal asphyxia are neuroprotective, and a well‐tolerated and feasible treatment for infants following hypoxic ischaemic encephalopathy. Abstract: Perinatal asphyxia is a significant cause of death or long‐term neurodevelopmental impairment. Hypothermia, currently the only effective treatment, leads to modest improvements, but new therapeutic strategies are required. Umbilical cord blood (UCB) mononuclear cells have potent anti‐inflammatory properties and may reduce neuropathology. This study examined whether autologous UCB mononuclear cells were neuroprotective when administered to newborn lambs at 12 h after birth asphyxia. At caesarean section, birth asphyxia was induced by clamping the umbilical cord until mean arterial blood pressure decreased to 18–20 mmHg. Asphyxia ( n  = 20) or control ( n  = 11) lambs were resuscitated and maintained, with magnetic resonance spectroscropy (MRS) performed at 12 and 72 h, and were then killed at 72 h. Cord blood was collected once the cord was clamped, and mononuclear cells were isolated and labelled fluorescently and administered to control ( n  = 3) or asphyxia ( n  = 8) lambs. Asphyxia induced a significant increase in cellular apoptosis (caspase‐3 immunopositive) within all brain regions examined, including cortex, hippocampus, thalamus, striatum and subcortical white matter ( P  < 0.01  vs . control). Additionally, asphyxia induced significant and widespread astrogliosis and increased inflammatory cells (activated microglia and macrophages). The administration of UCB mononuclear cells (asphyxia+UCB) significantly decreased neuronal apoptosis, astrogliosis and inflammation ( P  < 0.05  vs . asphyxia alone). Asphyxia+UCB lambs also demonstrated decreased brain metabolites lactate:choline ( P  = 0.01) and lactate: N ‐acetylaspartate ( P  < 0.01) from 12 to 72 h, detected using MRS. Autologous UCB mononuclear cell treatment restores normal brain metabolism following perinatal asphyxia, and reduces brain inflammation, astrogliosis and neuronal apoptosis, supporting its use as a neuroprotective therapy following asphyxia. Key points: Asphyxia at the time of birth is a significant cause of death or disability in newborns. There is very limited treatment available for these newborns. Autologous umbilical cord blood (UBC) mononuclear cells reduce clinical markers of brain damage following perinatal asphyxia. Autologous UBC mononuclear cells reduce neuroinflammation and neuronal apoptosis within the brain following perinatal asphyxia. Autologous UBC mononuclear cells administered 12 h after perinatal asphyxia are neuroprotective, and a well‐tolerated and feasible treatment for infants following hypoxic ischaemic encephalopathy.